Perkembangan Fatayat NU Kabupaten Subang dalam Bidang Kaderisasi Periode 2015-2020 - Hidayat, Wiwit Nurhayati; Syahir, Amung Ahmad; Marliana, Dina (Historia Madania: Jurnal Ilmu Sejarah, 2020)
Fatayat NU is one of the Nahdlatul Ulama autonomous bodies. As we know, Nahdlatul Ulama is the largest sosial and religious social organization in Indonesia. Like its parent, Nahdlatul Ulama, now Fatayat NU has branches that are spread in almost every city in Indonesia, one of which is in Subang Regency. This study aims to determine how the history of Fatayat NU and the develompent of Fatayat NU Subang Regency, especially in the field of regeneratios for the 2015-2020 period. The method used this study is a qualitative method, namely by collecting data through literature, documentation and interview. The data analysis technique is done by the heuristic, criticism, interpretation and historiography methods. The results of the period 2015-2020 Fatayat NU Subang Regency succeeded inaugurating as many as 30 PACs throughout Subang Regency in 2019. Where as previously only 10 PACs were successfully appointed as cadres Fatayat NU Subang Regency.